Some cases of acute pulmonary edema due to severe altitude sickness - Bardalez Vega, Arturo (1955)
In this preliminary communication, we present seven cases of "serious acute pulmonary edema Soroche" observed by us at the American Hospital of Morococha. This casuistry, is in addition to the observations of Professors Carlos Monge and Alberto Hurtado, Einar A. Lundberg and lately, those contained in the thesis of Bachelor of Dr. Leoncio Lizarraga M.